Using FM Dyes to Study Endomembranes and Their Dynamics in Plants and Cell Suspensions - Jelínková, Adriana; Malínská, Kateřina; Petrášek, Jan (Methods in molecular biology (Clifton, N.J.), 2019)
FM (Fei-Mao) styryl dyes are commonly used for the fluorescence imaging of plasma membrane (PM) and endocytosis in vivo. Thanks to their amphiphilic character, these dyes are incorporated in the outer leaflet of the PM lipid bilayer and emit fluorescence in its hydrophobic environment. The endocytic pathway of FM dye uptake starts with rapid PM staining and continues in PM invaginations and membrane vesicles during endocytosis, followed by staining of trans-Golgi network (TGN) and ending in tonoplast (vacuolar membrane). FM dyes do not stain endoplasmic reticulum and nuclear membrane. The time-lapse fluorescence microscopy could track endocytic vesicles and characterize the rate of endocytosis in vivo. On the other hand, fixable FM dyes (FX) can be used for the visualization of particular steps in the FM dye uptake in situ. Staining with FM dyes and subsequent microscopic observations could be performed on both tissue and cellular level. Here, we describe simple procedures for the effective FM dye staining and destaining in root tip of Arabidopsis thaliana seedlings and suspension-cultured tobacco cells.
Keywords: Fluorescent Dyes; Endocytosis; Arabidopsis; fluorescenční mikroskopie; optické zobrazování; Plant Roots; Microscopy; endocytóza; BY-2; kořeny rostlin; Endomembranes; Cell Membrane; Microscopy, Fluorescence; Nicotiana; Optical Imaging; buněčná membrána; fluorescenční barviva; Arabidopsis thaliana root tip; tabák; Plasma membrane; FM styryl dyes